Inmigración en chile del paradigma económico al anacronismo jurídico. el caso de los inmigrantes haitianos (2020)
This papers explores the economic implications of immigration in Chile and how this country has tolerated and assimilated this phenomenon in a paradigmatic way in the region, a situation that is divergent with the anachronistic legislation and legal framework on migration in that country. The aforementioned causes harmful effe cts that, beyond the economic bounty and unquestionable capacity of Chile to tolerate large migratory volumes, point to a dangerous precedent for public migration policy, especially in the case of Haitian immigrants, which is contradictory with humanitarian criteria present in international instruments to which Chile has adhered. In this context, the article demonstrates how the chances of working for the most vulnerable migrant groups, contrary to what is thought in the intemational arena, have decreased, in many cases, due to differences in the demographic characteristics of immigrants and factors linked to xenophobia, social discrimination, and discrimination in the labor market, among others. Finally, it is recommended to reevaluate and update the current legislation on migration in Chile, so that, without prejudice to its ability to assimilate migration, that country implements immigration policies that, in opposition to what the current Govemment of Chile is deploying, keep in tune with juridical and constitutional principies, local and intemational, that protect the migrant worker and his family.